CONSUMER PROTECTION ON UNLIMITED WARRANTY TUPPERWERE PRODUCTS IN ISLAMIC LAW REVIEW IN MEKAR JAYA VILLAGE - Irvina, Ila (Archipelago Journal of Southeast Asia Islamic Studies, 2024)
Rapid economic development has produced various types and variations of goods or services. Islam clearly regulates what can and cannot be done in business activities, the Koran explains that rights and falsehood should not be mixed, if there is any doubt in making a choice it is recommended to leave. As is the case with business practices that are prohibited in Islam in the form of product or service fraud. In essence, Islam does not allow an activity of distribution and production of goods or services that does not provide information about goods or services honestly and transparently. The focus of the problem in this research is how the practice of unlimited guarantees for Tupperwere products in Mensem hamlet, Mekarjaya village, and how Islamic law reviews practices. Unlimited guarantee for Tupperwere products in Mensemat hamlet, Mekarjaya village. This research uses a qualitative method, namely research that uses methods, steps, and procedures that involve data and information obtained through respondents as subjects who can express their own answers and feelings to get a holistic general picture of the thing being studied. Based on the research results, in reviewing Islamic law regarding consumer protection in the unlimited guarantee for Tupperwere products, there is an element of non-disclosure between producers and consumers regarding the provision of guarantees. When the contract takes place, the manufacturer does not explain the warranty provisions in detail, giving rise to an element of gharar or fraud. Meanwhile, in this case, the contract does not fully meet the criteria for openness. Consumers do not get a guarantee letter when purchasing Tupperware products